Transparency Regarding the Tax Avoidance in Indonesia: A Philosophical Review - Yudi Yasmin Wijaya; A’an Efendi; Fanny Tanuwijaya; Nilna Aliyan Hamida (University of Jember, 2020)
Tax avoidance has become a significant problem that adversely impacts the state's financial system, and its impact can obstruct the state, resulting in distrust of the government. The distrust towards the government, generally due to the reason for tax avoidance. Tax avoidance is fundamentally people's awareness of economic democracy. In Indonesia, the current discussion refers to the Tax Procedure Act, specifically regulates the obligation of the taxpayer, but limiting the rights of taxpayers. It becomes a crucial problem of transparency as part of social rights. Although the activities indicate, democracy practice but other critical challenges affect its implementation. The state, as a people's forum, has an unrealized purpose and has the potential national disintegration. The potential of disintegration forms transparency in the taxation system. Transparency in the tax management can provide accountability between the government and citizens to maintain the effectiveness of tax administration. Using transparency in the taxation system is an excellent solution for a democratic economy. By using doctrinal research, tax transparency has aspects of being balanced to realize the welfare of the country. Balancing the features of the taxation system requires the right transmission to achieve the country's purpose for people's welfare. Keywords: Transparency, Tax Avoidance, Tax Law.